Evaluation Of The Local Regulations Draft Of Bengkulu Selatan Regency Concerning Local Taxes And Local Retributions By The Governor - Hendri Donan; Amancik Amancik; Ardilafiza Ardilafiza (Universitas Bengkulu, 2022)
Evaluation is the study and the assessment on the local regulation draft regulated in accordance with the law in the field of local government and other statutory regulations to find out if there are things that are contrary to the public interest, and/or higher legislation and/or decency. The evaluation on the local regulation draft in the regency/city area regarding local taxes and Local Retribution by the governor as a representative of the central government is a form of authority de-concentration delegated by the central government to the governor. The evaluation process is carried out before the relevant legal norms are binding on the general public. The central government gradually evaluates, tests, and even rejects the local regulation draft. Regarding the implementation of the evaluation, in practice it still creates complexities of obstacles in the evaluation of local regulation draft which actually has an impact on legal certainty, especially the legal interests of the district/city government. The problems of this research were how to evaluate the implementation of the Local Regulation Draft concerning Local Taxes and Local Retribution by the Governor and the obstacles in the implementation of the evaluation of the Local Regulation Draft concerning Local Taxes and Local Retribution by the Governor. The approach method used in this research was the normative legal method (juridical normative), while the analysis used was qualitative analysis. The data sources used were primary legal materials obtained through laws and regulations, and secondary legal materials sourced from various official documents. The results of the study indicate that the implementation of the evaluation of the local regulation draft in the regency/city area regarding local taxes and local retribution by the Governor seen from the role and authority of the institution has been in accordance with the legislation, but when viewed from the side of the procedures and time regulated in its implementation it has not been effective and does it not provide legal certainty. Obstacles in evaluating the local regulation draft in the regency/city area are the ineffectiveness of tiered supervision and the inaccuracy of time as stipulated in the legislation.